1996
DOI: 10.1103/physrevb.53.973
|View full text |Cite
|
Sign up to set email alerts
|

Depinning transition in Mott-Anderson insulators

Abstract: We have studied the I-V curves of amorphous insulators at very low temperature which exhibit a crossover from variable range hopping to a low-temperature activation law. Around a critical voltage V c , the current increases by several orders of magnitude. This is interpreted as resulting from an interplay between Coulomb interactions and disorder: below V c charges are collectively ''pinned,'' while above V c free charges exist. We find a critical scaling of the I-V curves near V c , at least when hysteretic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 17 publications
4
35
0
1
Order By: Relevance
“…Previous studies of electrical transport in such Y x Si 1−x samples [54]- [59], have shown that a small variation of x allows to cross the metal-insulator transition : above x ≃ 0.22 the samples are metallic; while for lower values of x, the samples exhibit an insulating behavior, i.e. a divergence of the resistance for T → 0, in agreement with the VRH predictions [55]- [58], except for the very weakly insulating samples at the lowest temperatures [59]. In the present work x ≃ 0.19 and the samples are strongly insulating, exhibiting VRH below T ≃ 2 K. Since the two samples we used behaved similarly, we report only the data of one of them.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of electrical transport in such Y x Si 1−x samples [54]- [59], have shown that a small variation of x allows to cross the metal-insulator transition : above x ≃ 0.22 the samples are metallic; while for lower values of x, the samples exhibit an insulating behavior, i.e. a divergence of the resistance for T → 0, in agreement with the VRH predictions [55]- [58], except for the very weakly insulating samples at the lowest temperatures [59]. In the present work x ≃ 0.19 and the samples are strongly insulating, exhibiting VRH below T ≃ 2 K. Since the two samples we used behaved similarly, we report only the data of one of them.…”
Section: Methodsmentioning
confidence: 99%
“…This modifies the zero-temperature I-V characteristics by an experimentally determined crossover function with a power-law temperature dependence. 27 A different approach was proposed in Ref. 13.…”
Section: A Semiclassical Regime V ͼ V Tmentioning
confidence: 99%
“…5 The current dependence Iϰ(VϪV b ) resulting from the effect of background charges was suggested 6 using ϭ1 in case of one-dimensional arrays, and ϭ5/3 in case of two-dimensional networks. That work has spawned a number of experiments [7][8][9][10][11] with in part different values of .…”
Section: Introductionmentioning
confidence: 99%